1990
DOI: 10.1111/j.1095-8649.1990.tb05610.x
|View full text |Cite
|
Sign up to set email alerts
|

Haematological response to reduced oxygen‐carrying capacity, increased temperature and hypoxia in goldfish, Carassius auratus L.

Abstract: Goldfish were exposed to three qualitatively distinct forms of respiratory stress: phenylhydrazine HCI-induced reduction in blood oxygen-carrying capacity; transient (3 h) hypoxia; and transient (I or 2 h) temperature-forced increases in oxygen demand. Response embodied three common features: ( I ) the relative number of immature red cells increased, and these were 'H-thymidine positive;(2) the abundance of apparently karyorrhectic or degenerating cells rose; (3) cells undergoing a form of division became prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 22 publications
(20 reference statements)
1
29
0
Order By: Relevance
“…The very rapid increase in haematocrit values of dorsal aorta blood within 12 h of Chaetoceros concavicornis treatment may have been due to division of erythrocytes (Murad et al 1990) and/or elevation of plasma catecholamine levels of the fish which could induce swelling of erythrocytes, entry of erythrocytes into the circulatory system from storage organs, such as the spleen, and plasma skimming under the influence of hypoxia (Ostroumova 1964, Johansen & Hanson 1967, Stevens 1968, Hughes 1981, Milligan & Wood 1986, Ishimatsu et a1 1988. Whatever the reason, the increased haematocrit concentrations observed in the present study were typical of those observed when teleost fish undergo hypoxia.…”
Section: Resultsmentioning
confidence: 99%
“…The very rapid increase in haematocrit values of dorsal aorta blood within 12 h of Chaetoceros concavicornis treatment may have been due to division of erythrocytes (Murad et al 1990) and/or elevation of plasma catecholamine levels of the fish which could induce swelling of erythrocytes, entry of erythrocytes into the circulatory system from storage organs, such as the spleen, and plasma skimming under the influence of hypoxia (Ostroumova 1964, Johansen & Hanson 1967, Stevens 1968, Hughes 1981, Milligan & Wood 1986, Ishimatsu et a1 1988. Whatever the reason, the increased haematocrit concentrations observed in the present study were typical of those observed when teleost fish undergo hypoxia.…”
Section: Resultsmentioning
confidence: 99%
“…Significant differences among data for normocythemic, anaemic and severely anaemic statesare indicated by different letters, as determined by repeated-measures ANOVA and Tukey-Kramer multiple-range test (P<0.05). and Davis, 1970;Smith et al, 1971;Chudzik and Houston, 1983;Houston and Keen, 1984;Murad et al, 1990;Marinsky et al, 1990;Gilmour and Perry, 1996;McClelland et al, 2005), other than those directly related to the anaemia itself. A single study on anaemic rats reported that the observed increase in coronary flow during cardiac contractions following PHZ treatment was prevented by an antioxidant, as well as reducing focal lesions in the muscle and the degree of hypertrophy (Meerson and Evsevieva, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Phenylhydrazine hydrochloride has been widely used to study experimental anaemia in a range of animals (Itano et al, 1976), including fish (Cameron and Wohlschlag, 1969;Cameron and Davis, 1970;Jones, 1971;Smith and Jones, 1982;Chudzik and Houston, 1983;Houston and Keen, 1984;Murad et al, 1990;Marinsky et al, 1990;Gilmour and Perry, 1996;McClelland et al, 2005 As there was some variability in the time for the onset of anaemia among fishes, sampling interval varied for each fish such that the anaemic and severe anaemic data were generally collected 24-72·h and 72-96·h, respectively, after injection. The maximal period for data collection postinjection for any fish was 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…Stored red cells are immediately released from the splenic reservoir (Pearson and Stevens 1991). Following this, rates of erythropoiesis and division of circulating juvenile cells and karyorrhexis rise (Murad, Houston and Samson 1990;Houston and Schrapp 1994). The former increase juvenile cell abundances.…”
Section: Fig Lbmentioning
confidence: 99%